Benefits of sealed-curing on compressive strength of fly ash-based geopolymers - Lee, S.; Van Riessen, Arie; Chon, C. (mdpi, 2016)
There is no standardized procedure for producing geopolymers; therefore, many researchers develop their own procedures for mixing and curing to achieve good workability and strength development. The curing scheme adopted is important in achieving maximum performance of resultant geopolymers. In this study, we evaluated the impact of sealed and unsealed curing on mechanical strength of geopolymers. Fly ash-based geopolymers cured in sealed and unsealed moulds clearly revealed that retention of water during curing resulted in superior strength development. The average compressive strength of sealed-cured geopolymers measured after 1 day of curing was a modest 50 MPa, while after 7 day curing the average compressive strength increased to 120~135 MPa. In the unsealed specimens the average compressive strength of geopolymers was lower; ranging from 60 to 90 MPa with a slight increase as the curing period increased. Microcracking caused by dehydration is postulated to cause the strength decrease in the unsealed cured samples. These results show that water is a crucial component for the evolution of high strength three-dimensional cross-linked networks in geopolymers.